Workers and Affections in a Historical Key A Review from Social History with Gender Perspective - D'Uva, Florencia (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2019)
This paper seeks to contribute to the reflection and knowledge of the History of Feelings and Emotions especially considering how these problematic topics have been approached in Labor History. It will take the case of a police report that took place in Las Flores town, in Buenos Aires province, to analyze the feelings, emotions, relations, values, expected standards of behavior, tensions and conflicts experimented and expressed by the subjects involved in this particular situation, paying special attention to class, gender and age marks implicated in their experiences.